Mirror for Humanity - Kottak, Conrad Philip (Boston, 2008)
The book is intended to provide a concise, relatively low-cost introduction to cultural anthropology. The combination of shorter length and lower cost increases the instructor's options for assigning additional reading case studies, readers, and other supplements-in a semester course. Based on experience with the first five editions, I can say that MFH also works well in a quarter system, since traditional cultural anthropology texts may be too long for a one-quarter course.
Keywords: Ethnology